Intraoperative ultrasound reduces the need for re-excision in breast-conserving surgery. Issue 1 (December 2015) - Karanlik, Hasan; Ozgur, Ilker; Sahin, Dilek; Fayda, Merdan; Onder, Semen; Yavuz, Ekrem
Abstract Background The purpose of this study was to evaluate ultrasound-guided surgery for palpable breast cancer by comparing the standard palpation-guided surgery in terms of the extent of healthy breast tissue resection, the percentage of tumor-free margins, and cosmetic outcomes. Methods This was a prospective, observational cohort study conducted from January 2009 to July 2011. Breast cancer patients, diagnosed via biopsy, were operated in guidance with either ultrasound or palpation. Patient demographics, tumor features, intraoperative findings, pathologic and cosmetic results, intraoperative-measured ultrasound margins, and pathology margins were compared. Results Ultrasound (US)-guided lumpectomy was performed on 84 women and palpation-guided lumpectomy on 80 women. Patient demographics and tumor characteristics showed no differences. The rate of re-excision was 17 % for the palpation-guided surgery group, and 6 % for the US-guided group (p  = 0.03). There was good correlation between the closest margins recorded by US and pathology margins (r  = 0.76, p  = 0.01). Volume of resection was significantly larger in the palpation-guided group despite the similar size of tumors (p  = 0.048). Cosmetic outcome of surgery was equivalent between groups. Conclusions Intraoperative ultrasound guidance for excision of palpable breast cancers is feasible and gives results in terms of pathologic margins that are comparable with those achieved by standard palpation-guided excisions.